The Notion and Attributes of Right – Terminating Legal Facts - KOSTRUBA, Anatoliy V. (Journal of Advanced Research in Law and Economics; Vol 10 No 1 (2019): JARLE Volume X Issue 1(39) Spring 2019DO - 10.14505//jarle.v10.1(39).26, 2019)
The paper shows that the basis for the formation of the right-terminating legal facts is laid by the understanding of what should be included in the domain of these facts. The authors demonstrate that the target for understanding the nature of right-terminating legal facts is the development form based on participation of the civilians in the legal relations. As the basis, the authors highlight the civil property legal relations. The paper underlines that the need for this emerges only in case the necessary environment is formed, which strives for self-realization and integrity, contributing to the higher integration of the state into the international structures and increase in the life quality of the population due to the increase in its legal culture. The novelty of the research is defined by the authors in the fact that they have first taken the measures aimed at the general regulation of the legal standards and systemic values of the legal culture of the country. It is noted that the same measures and forms are applied in the developed countries of the European Union. The authors include into the formation of integral environment the perceptions of the legal sources by the population, as well as define the possibility of stratification of the earlier set tasks on the regulation of the forms and methods of the civilians’ participation in court sessions.